2019
DOI: 10.1136/vr.104424
|View full text |Cite
|
Sign up to set email alerts
|

Potential new sources of hypoglycin A poisoning for equids kept at pasture in spring: a field pilot study

Abstract: Equine atypical myopathy in Europe results from hypoglycin A (HGA) exposure through the ingestion of samaras or seedlings of the sycamore maple tree. This pilot study aimed at better defining sources of HGA intoxication in spring. Samaras fallen on the ground and then seedlings were collected at two-week intervals from sycamore, Norway, and field maple trees over the spring 2016. In early April, rainwater from wet seedlings collected after a rainy night was harvested to be analysed. Mid-May, samaras of the box… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 20 publications
(54 reference statements)
0
11
0
Order By: Relevance
“…When in doubt, professional expertise should be sought to identify the tree (botanists and/or forestry agents might be of help). Recently, it has been suggested that flowers falling from sycamore trees after heavy rainfall and/or wind could be an additional source of intoxication [26].…”
Section: Avoid Contact With Toxic Plant Materialsmentioning
confidence: 99%
See 4 more Smart Citations
“…When in doubt, professional expertise should be sought to identify the tree (botanists and/or forestry agents might be of help). Recently, it has been suggested that flowers falling from sycamore trees after heavy rainfall and/or wind could be an additional source of intoxication [26].…”
Section: Avoid Contact With Toxic Plant Materialsmentioning
confidence: 99%
“…However, when samaras are too abundant and/or too widely dispersed within the premise, grazing in the affected area must be prohibited. Another way to limit grazing to areas free of fallen seeds and/or flowers and/or seedlings is to create parcels within the pasture [26].…”
Section: Avoid Contact With Toxic Plant Materialsmentioning
confidence: 99%
See 3 more Smart Citations